THEORETICAL ASPECTS OF STRATEGY IN IMPLEMENTATION INNOVATIVE DEVELOPMENT OF THE ENTERPRISE (Development Service Industry Management, 2024)
New challenges for enterprises determine the need to change approaches to the formation of their strategy. The process of strategizing itself is transformed according to business demands and the influence of the environment. Fierce competition in the markets determines the need to understand both the theoretical foundations of strategizing and the applied aspects of developing specific strategies. The article presents the interpretation of the concept of "strategy" by the most famous specialists in this field, they interpret it as an action plan aimed at achieving specific goals or tasks in certain conditions. The strategy can cover various areas of the organization's activity, but it is worth noting that the company's strategy is closely related to the competitive strategy, and their successful interaction allows the company to ensure its stability in the market and achieve competitive advantages. The process of forming a competitive strategy includes a number of consecutive steps: formation of a mission, goals, assessment of the external environment, management analysis of strengths and weaknesses, analysis of strategic alternatives, strategy selection, strategy implementation, strategy evaluation. It was determined that the basis of strategizing is the company management's vision of ways of innovative development of the enterprise in the long term. It has been proven that the market and technological positions of the enterprise influence approaches to innovative strategies. Depending on these positions, companies can choose different directions of development and innovation. Competitive strategies and innovation strategies ensure the very process of strategizing depending on the actual conditions of the enterprise's functioning and the propensity of the owners and management to risk and the introduction of innovations. Competitive and innovative strategies make it possible to solve this issue due to a comprehensive approach to defining strategic goals and a systematic study of alternative approaches to enterprise management in conditions of uncertainty.
Keywords: strategy; innovation; development; planning; business